1999
DOI: 10.1136/bmj.318.7184.647
|View full text |Cite
|
Sign up to set email alerts
|

Published criteria for evaluating health related web sites: review

Abstract: Objective To review published criteria for specifically evaluating health related information on the world wide web, and to identify areas of consensus. Design Search of world wide web sites and peer reviewed medical journals for explicit criteria for evaluating health related information on the web, using Medline and Lexis-Nexis databases, and the following internet search engines: Yahoo!, Excite, Altavista, Webcrawler, HotBot, Infoseek, Magellan Internet Guide, and Lycos. Criteria were extracted and grouped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
368
0
15

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 434 publications
(385 citation statements)
references
References 14 publications
2
368
0
15
Order By: Relevance
“…Similar approaches have been used for evaluating other healthrelated web sites. 24 Content abstraction included hospital accreditation and quality measures, defined as self-identified awards or markers of excellence, or measures for quality improvement. Some measures could be verified.…”
Section: Data Abstractionmentioning
confidence: 99%
“…Similar approaches have been used for evaluating other healthrelated web sites. 24 Content abstraction included hospital accreditation and quality measures, defined as self-identified awards or markers of excellence, or measures for quality improvement. Some measures could be verified.…”
Section: Data Abstractionmentioning
confidence: 99%
“…These are important principles to ensure quality and reliability of site content (15,17) . Technical scores revealed that disease prognosis was frequently not addressed in the studied sites (44.9%).…”
Section: Discussionmentioning
confidence: 99%
“…Many organisations have published criteria to help individuals assess the quality of health-related websites but there is no standard set of guidelines. 4 Journals Reading journals is obviously one method of keeping track of the latest advances in your field of interest. There is a range of journals in both general dentistry and in the various specialties.…”
Section: Sources Of Evidencementioning
confidence: 99%